1998
DOI: 10.1017/s1357729800009437
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental causes of variation in milk production traits of Sahiwal cattle in Pakistan

Abstract: Data from about 4000 Sahiwal cows from eight large herds in Pakistan were used to study the influence of genetic and environmental factors on some milk production traits. First-lactation mean values were 1363 kg, 1395 kg and 252 days for milk yield up to 305 days after calving, total lactation yield and lactation length, respectively. Second and third lactation yields were proportionately 0-12 and 0-18 higher, respectively, at 305 days. The effect of herdyear at calving was by far the most important source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
2
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 22 publications
10
30
2
1
Order By: Relevance
“…The findings of the present study are in line with earlier reports on Sahiwal cattle in Pakistan (DAHLIN et al, 1998). A higher first lactation 305-day milk yield (2,083 ± 33 kg) based on 580 observations have been reported by BHATNAGAR et al (1983) for Indian Sahiwal.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of the present study are in line with earlier reports on Sahiwal cattle in Pakistan (DAHLIN et al, 1998). A higher first lactation 305-day milk yield (2,083 ± 33 kg) based on 580 observations have been reported by BHATNAGAR et al (1983) for Indian Sahiwal.…”
Section: Discussionsupporting
confidence: 93%
“…However, MOHIUDDIN et al (1991) and JAVED (1999) have reported this correlation as 0.44 and 0.60, respectively. Genetic correlation between first lactation milk yield and lactation length has been reported from 0.23 to 0.83 (DAHLIN et al, 1998;JAVED, 1999 andCHOUDHARY et al, 2003). Materials and Methods Data on performance traits of Sahiwal Cattle from five main Governmental herds i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lactation yield is usually calculated as the sum of daily milk yield a cow produces in a particular lactation. No restrictions were imposed on the minimum TD and lactation length because of the considerable variation in lactation length and daily milk yield in B. indicus breeds (Madalena, 1988;Maule, 1990;Rege et al, 1992;Dahlin et al, 1998). As a result, the number of TD records were variable throughout the eight TD (Table 1).…”
Section: Data Sourcementioning
confidence: 99%
“…The Sahiwal breed is known to have the greatest potential for milk production, growth and reproductive efficiency in tropical environments compared with other Bos indicus breeds (Mwandotto, 1994;Dahlin et al, 1998;Khan et al, 1999;Muhuyi et al, 1999). Its ability to endure and produce in harsh environments coupled with its dual-purpose role has widened the distribution of this breed in tropical and subtropical countries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Pakistan there are~25 million dairy cattle, but the most established progeny testing system in the country records <1000 milking animals per year. Furthermore, in developing dairy sectors, problems can be exacerbated due to the large environmental effects, poor management due to limited resources and poor data quality (Dahlin, 1998;Ilatsia et al, 2007). These problems have their implications and potentially reduce genetic gain.…”
Section: Introductionmentioning
confidence: 99%